The accreditation and implementation of the formal literacy route in a post apartheid South Africa : an investigation into how the ABET route fulfills the needs of the adult learner, the corporate sector and the economic development of South Africa - Vivian, Brenda Ann (2012)
M.A. === Even before the first democratic elections in South Africa in 1994, many Non-Governmental Organisations carried the torch of literacy for those South Africans who were not given the opportunity to learn to read and write, due to the inequalities of the apartheid education policies. Subsequent to the 1994 elections, the government took steps to formalise literacy initiatives and, in so doing, create national standards. Hence the birth of Adult Basic Education and Training. With the emergence of the South African Qualifications Authority, the ABET route was integrated into the National Qualifications Framework as part of the overall vision for standardised education in South Africa. Presently, the ABET route is mainly sponsored by the private sector who have shouldered the costs of these adult literacy initiatives. The formal ABET route is assessed by the Independent Examinations Board. This study illustrates how the formal ABET route does not adequately meet the goals of the department of Education in terms of its goals for reconstruction and development, nor does it guarantee the learner an improved future life, nor does it provide the private sector with the competencies they had hoped for in the workplace. Two of the most significant shortcomings of the formal ABET route were found to be the assessment process and the difficulty of the facilitation between the ABET route and qualification on the NQF. Based on the findings of this research, recommendations have been made. These aim to improve the flexibility of the ABET route and provide a number of options which may be more suitable for the needs of the learners, the corporate sector and the economy of South Africa as a whole.